Peripherally Inserted Central catheter iNnovation to reduce Infections and Clots (the PICNIC trial): a randomised controlled trial protocol. Issue 4 (14th April 2021) - Ullman, Amanda J; August, Deanne; Kleidon, Tricia; Walker, Rachel; Marsh, Nicole M; Bulmer, Andrew; Pearch, Benjamin; Runnegar, Naomi; Schults, Jessica A; Leema, Joanne; Lee-Archer, Paul; Biles, Cathy; et al.
Abstract : Introduction: Peripherally inserted central catheters (PICCs) are vital for the delivery of medical therapies, but up to 30% of PICCs are associated with complications such as deep vein thrombosis or infection. The integration of antimicrobial and hydrophobic catheter materials, and pressure-activated valves, into polyurethane PICCs are innovations designed to prevent infective and/or thrombotic complications. Methods and analysis: A multicentre, parallel group, superiority randomised controlled trial with two experimental arms ((1) hydrophobic PICC (with pressure-activated valve); (2) chlorhexidine gluconate-impregnated PICC (with external clamp)) and one control group ((3) conventional polyurethane PICC (with external clamp)). Recruitment of 1098 adult and paediatric patients will take place over 2 years at three tertiary-referral hospitals in Queensland, Australia. Patients are eligible for inclusion if their PICC is to be inserted for medical treatment, with a vascular size sufficient to support a 4-Fr PICC or larger, and with informed consent. The primary outcome is PICC failure, a composite of thrombotic (venous thrombosis, breakage and occlusion) and infective complications (PICC-associated bloodstream infection and local infection). Secondary outcomes include: all-cause PICC complication; thrombotic complications; infective complications; adverse events (local or systemic reaction); PICC dwell time; patient/parent satisfaction; and healthcare costs. Differences between both intervention groups and the control group will be compared using Cox proportional hazards regression. Effect estimates will be presented as HRs with corresponding 95% CI. Ethics and dissemination: Ethical approval from Queensland Health (HREC/QCHQ/48682) and Griffith University (Ref. No. 2019/094). Results will be published. Trial registration number: ACTRN12619000022167.